INVESTASI REKSADANA SYARIAH DI INDONESIA - Andriani, Fitria (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2020)
The development of Islamic investment in Indonesia is progressing very rapidly. The principle of every investment made by each individual must be based on sharia principles. This study aims to explain the principles of sharia mutual funds investing which are currently growing rapidly as well as the development and procedures for investing in Islamic mutual funds. The results of this study indicate that the statistical development of Islamic mutual funds tends to increase significantly, the NAV of Islamic mutual funds in August 2020 reached 67.71 trillion. Players in sharia mutual fund investments include investors and investment managers who are trusted by investors in managing their mutual funds. The procedure for investing in Islamic mutual funds includes two ways, namely the method of buying or referred to as subcription and redemption or the method of selling Islamic mutual funds, a good understanding of these two methods will determine the risks and benefits that investors and investment managers get. Keyword: Mutual Fund Investment, Investment Procedures. Abstrak Perkembangan investasi syariah di Indonesia melaju dengan sangat pesat, Prinsip dari setiap investasi yang dilakukan oleh setiap individu harus berlandaskan dengan prinsip syariah. Penelitian ini bertujuan untuk menjelaskan prinsip dari investasi reksadana syariah yang saat ini sedang berkembang pesat serta perkembangannya dan tata cara melakukan investasi pada reksadana syariah. hasil penelitian ini menunjukkan perkembangan statistik reksadana syariah cenderung naik signifikan, NAB reksadana syariah agustus 2020 mencapai 67,71 Triliun. Pelaku dalam investasi reksadana syariah meliputi investor dan manajer inverstasi yang dipercayai oleh investor dalam mengelola reksadana miliknya. Tata cara investasi pada reksadana syariah meliputi dengan dua cara yaitu cara pembelian atau disebut dengan subcription dan redemtion atau cara penjualan pada reksadana syariah, pemahaman yang baik akan kedua cara ini akan menentuan resiko dan keuntungan yang di dapatkan oleh investor dan manajer investasi. Kata kunci: Investasi Reksadana, Tata Cara Invetasi Reksadana.